THE LEGACY AND CONTRIBUTIONS OF DALIT LEADERS: A FOCUS ON RETTAMALAI SRINIVASAN, AYOTHIDASA PANDITHAR, KAKAN, AND VEERA MANGAI KUYILI - P. Prabakaran; G. Paranthaman (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This research explores the profound impact of Dalit leaders in Indian history, specifically focusing on four prominent figures: Rettamalai Srinivasan, Ayothidasa Pandithar, Kakan, and Veera Mangai Kuyili. These individuals played crucial roles in shaping the social, cultural, and political landscape of Tamil Nadu and India by challenging caste-based discrimination and advocating for the rights of Dalits. This article delves into their contributions, examining their activism, ideologies, and the socio-political contexts in which they operated. By analyzing their work, this study aims to shed light on the often-overlooked legacy of these figures and highlight their significance in the larger Dalit emancipation movement.